2017
DOI: 10.13189/ujp.2017.050405
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Emotion-focused Cognitive Therapy in Decreasing Depression due to Marital Relationship Problems

Abstract: Marital distress and marital relationship problems are effective in generation and acceleration of depression. Depression is a significant contributor to the global burden of disease and affects people in all communities across the world. This study aims to determine the effectiveness of emotion-focused cognitive therapy in decreasing depression caused due to marital relationship problems. The design of this study was semi-experimental with pre-test, post-test and control group. The research population consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In line with the present study, Hashemi and Kimiaei found emotion-focused cognitive therapy to reduce the depression caused by marital problems and the patterns of mutual avoidance and demand/withdraw in the intervention group (35) and Mahlabani Gorgian et al found emotion-focused couple therapy to be eff ective in treating the depression caused by couples' communication prob-lems (36).…”
Section: Discussionsupporting
confidence: 85%
“…In line with the present study, Hashemi and Kimiaei found emotion-focused cognitive therapy to reduce the depression caused by marital problems and the patterns of mutual avoidance and demand/withdraw in the intervention group (35) and Mahlabani Gorgian et al found emotion-focused couple therapy to be eff ective in treating the depression caused by couples' communication prob-lems (36).…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, the findings cannot be applied to non‐Western countries and not even to ethnically diverse populations in Western countries. Actually, the search identified some Iranian studies, not included due to methodological shortcomings (e.g., Hashemi & Kimiaei, 2017). This means there is a need to provide evidence to inform practice also in low‐ and middle‐income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Control conditions in the studies on couple interventions for depression included treatment as usual ( n = 3; Adler et al, 2018; Seikkula et al, 2013; Wittenborn et al, 2019), waitlist ( n = 2; Cohen et al, 2010; Hashemi & Kimiaei, 2017), and medication management ( n = 1; Denton et al, 2012). One study (Adler et al, 2018) also included a non‐randomized community comparison group.…”
Section: Resultsmentioning
confidence: 99%
“…Two of six studies on couple interventions for depression (Cohen et al, 2010; Hashemi & Kimiaei, 2017) compared the experimental condition (i.e., Brief, Problem‐Focused Couple Therapy for Depression, Emotion‐Focused Cognitive Therapy) to a waitlist control condition. In both studies, on average, participants in the experimental condition reported significantly greater improvement in depressive symptoms compared to participants in the waitlist condition.…”
Section: Resultsmentioning
confidence: 99%